HUBUNGAN DISIPLIN MAHASISWA DAN FASILITAS KAMPUS DENGAN PRESTASI MAHASISWA - Didi C. Chalil (Jurnal Manajemen Kewirausahaan, 2018)
One indicator of the success ofeducation in the level of classroom learning is when a lecturer is able to build student learning achievement and will be more successful if this achievement can be increased if their attendance is above 80% (minimum 10 times attendance from 12 meetings). If the students can be grown discipline and provided a decent campus facilities, then as difficult as any lecture material or learning process that followed by they undoubtedly will live with feelings of joy, even they will feel sad if that day lecturer could not come because there is a need outside campus.There are four stages of appraisal that apply to each student for each course taken include (1) attendance of 10% (2) Task 20% (3) 30% Semester Exam (UTS) and (4) Final Exam Semester. (UAS) 40%. The writer as a lecturer tries to cultivate motivation to learn from the beginning, in addition to always communicate actively with students who follow the lecture also monitor attendance and assignment, each completed college is always given the practice / tasks are directly given the value, usually given the task quite easily so they can get a value of 100, even if there is a miscalculation, they are still given the opportunity to fix the error so that eventually get a value of 100. With the value of this 100, their motivation to grow and even grow in such a way that spur them to diligent lectures.The difficulty level of the task is balanced with the lecture, the longer it is raised so as to reach the maximum average level of student ability at the end of the lecture meeting...This research reveals that there is no a significant correlation between student achievement to discipline presence of student/mahasiswa with campus facilities. The analyzing was taken from an answer of 55 students who were randomly selected as respondents by filling out the Questionaire that was distributed to them.Â Key words : achievement, attendance, discipline, campus facility